Website-Based Sales Transaction Data Monitoring Information System - Arfika Putri Risandi; Herliyani Hasanah; Intan Oktaviani (Komunitas Dosen Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to the Indonesian economy, yet many still rely on manual transaction recording using Excel, which often results in errors, delays in reporting, and difficulties in accessing historical sales data. These limitations hinder effective decision-making and reduce operational efficiency. In response to these challenges, this study aims to develop a website-based sales transaction data monitoring information system that enables real-time monitoring and structured data management for various user roles: admin, reseller, and leader. The system was developed using the Rapid Application Development (RAD) method, which emphasizes fast prototyping and user feedback to ensure functionality meets actual needs. Features include automated Excel data uploads, interactive dashboards, and reseller performance visualizations tailored to user roles. Testing was conducted using Black Box Testing and User Acceptance Testing (UAT). The results indicate that all system functions operated according to design specifications and received positive feedback from users regarding usability and effectiveness. The implementation of this system successfully addresses the common problems faced by MSMEs in transaction management by improving accuracy, speeding up reporting, and enhancing monitoring transparency. In conclusion, this system offers a practical solution that is ready to be adopted by MSMEs with similar transaction recording issues, supporting digital transformation and operational efficiency in the MSME sector.